Hubungan Antara Persepsi Profesionalisme Guru PAI dan Motivasi Belajar PAI dengan Pembentukan Kepribadian Peserta Didik - Benny Prasetiya (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2015)
The study also sought to determine the contribution of students' perceptions about the professionalism of teachers and learning motivation of Islamic religious education to the formation of the Islamic Personality of learners. Together the students' perception of the professionalism of teachers and learning motivation of Islamic religious education related to the establishment of the Islamic Personality. Results of multivariate analysis with multiple regression which has a dominant role and significantly associated with the formation of the Islamic personality, that students' perceptions about the professionalism of teachers and learning motivation of Islamic religious education. Party authorities and teachers are expected to pay attention to these factors either the professionalism of teachers and learning motivation of Islamic religious education, so as to support the achievement of the formation of Islam with a good personality. The results could be implicated to learners in particular to improve the professionalism of teachers and learning motivation of Islamic religious education in order to overcome the obstacles in penguasaaan science of Islamic education in the formation of the Islamic personality.